Selenium and Human Health - Gelen, Volkan; Kara, Adem; Kükürt, Abdulsamed (IntechOpen, 2023)
Selenium is a powerful trace element and antioxidant with multiple effects on metabolism and human health. Available as a dietary supplement for many years, it is one of the most popular over-the-counter alternative medicines available. Written by researchers in the field, this comprehensive book offers a wide range of expert reviews on the role of selenium in a variety of diseases as well as the effects of selenium on human health.